Irony as Social Criticism in Instagram Comments: A Study on “Liga Korupsi Indonesia” - Giyatmi; Arumi, Sihindun; Wijayava, Ratih (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
Irony is often employed as a form of social criticism, particularly in online discourse. This study examines the function of irony in comments on the Instagram Reel Liga Korupsi Indonesia (LKI). This qualitative descriptive study aims to identify the various roles irny plays in user comments on the Instagram Reel “LKI” The qualitative descriptive method is appropriate as it allows an in-depth exploration of irony as a linguistic phenomenon within the context of social media interactions. In accordance with the problems in this study, the writers use theories related to the function of irony found from several articles discussing the function of irony from several perspectives. Data, ironic comment, were collected through documentation and content analysis, while triangulation was ensured through methodological and theoretical approaches. The writers identified six primary functions of irony in the comments: (a) a subtle form of criticism (12 out of 76), (b) intensifying condemnation or "salting a wound" (6 out of 76), (c) humour and social bonding (18), (d) emotion regulation (8 out of 76), (e) a persuasive tool in debate and discussion (9 out of 76), and (f) balancing praise and blame (23 out of 76). Among these, irony as a balance between praise and blame emerged as the most frequently used function, indicating that netizens prefer a diplomatic approach to criticism rather than outright confrontation. Conversely, irony employed to intensify condemnation was the least frequent, as its confrontational nature often leads to conflict and unproductive debate. The study highlights how irony serves as an effective tool for nuanced social critique in digital spaces.